2016
DOI: 10.1016/j.ajpath.2015.10.023
|View full text |Cite
|
Sign up to set email alerts
|

The Challenge of Cancer Genomics in Rare Nervous System Neoplasms

Abstract: Comprehensive genomic analyses of common nervous system cancers provide new insights into their pathogenesis, diagnosis, and treatment. Although analogous studies of rare nervous system tumors are needed, there are major barriers to performing such studies. Cross-species comparative oncogenomics, identifying driver mutations in mouse cancer models and validating them in human tumors, is a promising alternative. Although still in its infancy, this approach is being applied to malignant peripheral nerve sheath t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 101 publications
(78 reference statements)
2
31
0
Order By: Relevance
“…Neurofibromatosis is a syndrome with Schwann cell-derived tumors caused by loss of either the NF1 or NF2 tumor suppressors (Carroll 2016). Loss of NF1 is associated with an increased risk that the disease progresses from benign neurofibromas to malignant peripheral nerve sheath tumors (MPNST’s).…”
Section: Discussionmentioning
confidence: 99%
“…Neurofibromatosis is a syndrome with Schwann cell-derived tumors caused by loss of either the NF1 or NF2 tumor suppressors (Carroll 2016). Loss of NF1 is associated with an increased risk that the disease progresses from benign neurofibromas to malignant peripheral nerve sheath tumors (MPNST’s).…”
Section: Discussionmentioning
confidence: 99%
“…Nf1 −/− E1A-p53 MEFs were created by transforming MEFs harboring a germline bi-allelic inactivating Nf1 mutation, with an E1A oncogene and dominant-negative p53 (8). Such transformation partially recapitulates p53 and Rb inactivation that are often seen in NF1-associated malignancies (9, 10). …”
Section: Resultsmentioning
confidence: 70%
“…22, 23, and Figure 2B). In addition, key signaling pathways in MPNSTs, including the Wnt/β-catenin, PI3K/AKT/mTOR, and RAS pathways (1,2), were also enriched ( Figure 2, B-D, and Supplemental Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…HuR regulates key cell cycle genes in MPNSTs via an RB/E2F axis. RAS/MEK/ERK and PI3K/AKT/mTOR are 2 other major signaling pathways that are upregulated in MPNSTs and have important roles in MPNST pathogenesis (1,2). GSEA analysis revealed that many components of these pathways were significantly downregulated by HuR silencing, including activation of receptor tyrosine kinases such as PDGF (Supplemental Figure 9, A and B).…”
Section: St88-14 Mpnst Cells (Supplementalmentioning
confidence: 99%
See 1 more Smart Citation